Western and Islamic Perspective Epistemology - Siti Chairun Nisya; Aina Nur Hilmy; Doni Doni; Salminawati Salminawati (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This research aims to discuss epistemological issues by focusing on several key epistemological concepts, such as the meaning of science, objects of knowledge, sources of information, validity of science, and appropriate methods for obtaining and using knowledge. We will first discuss the idea of epistemology as a subfield of philosophy before turning to epistemological principles in Islamic and Western contexts. The study of epistemology, which is often called Theory of Science, is very important for the progress of a country's civilization and culture. Every culture develops an epistemology according to its worldview. As a result, each civilization—including Islamic and Western epistemologies—has its own epistemology. There is a unique principle that distinguishes these two epistemologies. Their different worldviews explain the real differences between Islamic and Western epistemologies. Islamic epistemology is based on the study of metaphysics, while Western epistemology is based on assumptions. Islamic epistemology refers to the Koran, common sense, the five senses, and intuition, while Western epistemology exclusively considers reason (ratio) and empirical facts as sources of knowledge.